Laparoscopic treatment of pyogenic liver abscess complicating Crohn’s disease: A case report - (:unkn) unknown (My University, 2007)
Crohn hastalığına bağlı piyojenik karaciğer absesi yaygın de- ğildir, fakat teşhis ve tedavi geciktiğinde ölüm oranı yükselmektedir. Burada, Crohn hastalığının bir komplikasyonu olarak karaciğer sağ lobda multi-loküler abse gelişmiş, 42 yaşında bir erkek hasta sunulmuştur. Acil ünitesine başvurusunda hastada sağ üst kadran ağrısı, 39°C ateş ve hepatomegali tespit edildi. Yapılan karın ultrasonografi ve bilgisayarlı tomografisinde karaciğer sağ lobda multi-loküler piyojenik abse gösterildi. Pürülan mayinin yoğunluğunun fazla olması nedeniyle perkütan drenaj başarısız oldu, sonrasında laparoskopik eksplorasyon yapılarak 1500 ml abse başarılı bir şekilde drene edildi. Ameliyat sonrası üçüncü günde ateşi ve lökositozu düzelen hasta klinik olarak iyileşti.

Pyogenic liver abscess in patients with Crohn’s disease is not common, but the mortality has been reported to be high if diagnosis or treatment is delayed. Herein, we report the case of a 42- year-old man in whom multi-locular liver abscess was encountered in the right lobe of the liver as a complication of Crohn’s disease. On his admission to the emergency unit, he had right upper quadrant pain, fever of 39°C and hepatomegaly. Ultrasonography and abdominal computerized tomography demonstrated multi-locular pyogenic liver abscess in the right lobe of the liver. Percutaneous drainage failed because of the density of the pus; laparoscopic exploration was subsequently performed and 1500 ml pus was successfully drained. The patient became clinically stable without fever and with a decreasing white blood cell count on the third postoperative day.
Crohn hastalığına bağlı gelişen piyojenik karaciğer apsesinin laparoskopik tedavisi: Bir olgu sunumu
Keywords: Cerrahi